Дослідження потенційних можливостей застосування LoRa модуляції в супутникових каналах зв'язку - Дмитренко, В. В. (ХНУРЕ, 2024)
Growing network of Internet of Things (IoT) beyond the cities and quantity of Low Earth Orbit (LEO) satellites makes us to think about abstraction from building usual cellular networks or base stations for IoT in the field, especially when we speak about inaccessible nodes of data collection or if it’s situated far from places of people living. When we need get power from battery and sun and think globally, it’s clear to use LEO satellites for building IoT network for far away sensors or things. LoRa is that special wireless platform which allow us to access satellites on LEO with limited power.
Keywords: супутниковий канал зв'язку; застосування LoRa модуляції